ASSOCIATION OF CORD HEPCIDIN AND IRON PARAMETERS WITH MATERNAL HEPCIDIN, IRON STATUS MARKERS AND NEONATAL MORPHOMETRICS - Najeeb, Tabinda; Anjum, Nargis (Pakistan Journal of Physiology, 2018)
Background: Hepcidin is the only iron regulating hormone in human body. The foetus begins to synthesize Hepcidin from the 1st trimester of gestation to control unidirectional iron transfer from mother to foetus. The objective of the present study was to determine the correlation of cord Hepcidin with iron status markers of mothers, neonates and neonatal morphometrics. Method: Twenty-five healthy pregnant women and their neonates were included in the study. Haemoglobin, Iron status markers and Hepcidin were analyzed in maternal and cord blood. Neonatal anthropometric variables were measured. Pearson/Spearman correlation was used for association of different variables of mother-neonate pairs. Results: Maternal Hepcidin showed positive correlation with maternal Iron, Ferritin and Transferrin Saturation (TS) (r=0.455 and p=0.022, r=0.511 and p=0.009, r=0.440 and p=0.025 respectively). Cord Hepcidin was positively correlated with cord iron, Ferritin and Transferrin saturation (r=0.593 and p=0.002, r=0.792 and p=0.000, r=0.546 and p=0.005 respectively). Neonatal morphometric variables were neither correlated to cord Hepcidin nor with any other Cord blood variable. Maternal Ferritin showed positive correlation with cord Haemoglobin (r=0.456, p=0.022) and cord Ferritin (r=0.460, p=0.021). Conclusion: There was no correlation between cord Hepcidin and neonatal morphometrics. Maternal and neonatal Hepcidin are independent of each other in iron status regulation. Pak J Physiol 2018;14(2):7–10